Design of a geographic information system (gis) for the spread of covid-19 disease in medan city - Melania Justice Panggabean; Yulita Molliq Rangkuti; Ichwanul Muslim Karo-Karo (Institute of Computer Science (IOCS), 2023)
The world is currently facing an outbreak of the corona virus (Covid-19). Covid 19 is a group of highly diverse, enveloped, single-stranded RNA viruses. This disease causes respiratory tract infections in humans with severity ranging from mild to fatal. Examples of mild illnesses such as influenza while for deadly diseases such as MERS and SARS. Medan city is one of the areas that is prone to Covid-19 disease. Where the spread of Covid-19 has reached 16.4% the positive case rate with an assessment of the Covid-19 situation as of February 2022 is at Level 4. So, we need a sytem that can monitor the progress of the case. The purpose of this research is to build a geographic information sytem using the Fuzzy C-Means method and integrate GeoJSON to map the spread of the Covid-19 disease in Medan City. The results of clustering calculations using the Fuzzy C-Means method yield the following results: Cluster 1 which contains the sub-districts of Medan Amplas, Medan Area, Medan Baru, Medan Barat, and Medan Perjuangan is in the green zone. Cluster 2 which contains the sub-districts of Medan Denai, Medan Tembung, Medan Petisah, Medan Kota, and Medan Timur is in the red zone. Cluster 3 which contains the sub-districts of Medan Tuntungan, Medan Selayang, Medan Johor, Medan Sunggal, and Medan Helvetia is in the orange zone. And Cluster 4 which contains the sub-districts of Medan Polonia, Medan Maimun, Medan Deli, Medan Labuhan, Medan Marelan, and Medan Belawan is in the yellow zone.